Microstructure and physical properties of combined plastic-cementitious artificial aggregate. Issue 1 (October 2021) - Sumarsono, RA; Anisah,; Utami, A N T; Wilfadz, M; Permana, A
Abstract: Over the years, the availability of natural construction material has been critical. Plastic has been taken into consideration for replacement of natural aggregate; however, the result is not satisfying. Furthermore, some cementitious materials are also proposed for the artificial aggregate due to its mineral, but the production process is high energy consumption. The idea of combining plastic and cementitious material in terms of polyethylene terephthalate (PET) and diatomaceous earth soil (DE) is proposed in this paper. Henceforth, the artificial aggregate is named as PETOM (PET and DE) and DIAHPET (PET, HDPE, and DE). Molten blending for both PET and DE with various proportion at 325°C has resulted in new type of artificial aggregate with gross surface especially DIAHPET. Further investigation using Scanning Electron Microscope (SEM), the micro structure of PETOM with greater diatomite serves more pores, but DIAHPET is astonishingly dense with sheer pores. Specific gravity of PETOM and DIAHPET is 1.31-1.46 gr/cm 3 and 1.12-1.25 gr/cm 3, respectively. The density value directs to the lightweight aggregate category with the highest value of 843 kg/m 3 . The highest compressive strength of PETOM and DIAHPET aggregate gained is 9 MPa and 7 MPa, consecutively. These plastic-based aggregates are feasible for coarse aggregate of lightweight concrete.